Source of two-dimensional electron gas in unintentionally doped AlGaN/GaN multichannel high-electron-mobility transistor heterostructures—experimental evidence of the hole trap state - Lingaparthi, R. (2023)
Multichannel high electron mobility transistor (MC-HEMT) heterostructures are one of the choices for improved power performance of GaN HEMTs. By comparing the experimentally obtained two-dimensional electron gas (2DEG) concentration of unintentionally doped (UID) AlGaN/GaN MC-HEMTs with simulated 2DEG concentration, we hypothesized that hole trap(s) exist at the buried GaN/AlGaN interfaces, which act as sources of 2DEG in UID MC-HEMT heterostructures. Furthermore, these hole traps stop the Fermi level from cutting the valence band at GaN/AlGaN interfaces, which in turn precludes the generation of parallel two-dimensional hole gas (2DHG) in the MC-HEMT. However, no experimental report is present as a proof for the existence of such a hole trap in MC-HEMT heterostructures. In this study, a capacitance-conductance method on single and dual channel HEMTs revealed traps with higher time constant of 19-28.7 μs exclusively for the dual channel HEMT heterostructure. These traps are observed at the buried GaN/AlGaN interface of the dual channel HEMT; hence, they are attributed to possible hole traps at this interface. By conducting systematic deep level transient spectroscopy measurements, the existence of hole traps is confirmed at the buried GaN/AlGaN interface with an activation energy of 717 meV and a capture cross section of 1.3 × 10−14 cm2. This experimental evidence of the existence of hole traps at the GaN channel/AlGaN interface further supports our claim that these hole traps act as the source of 2DEG in UID MC-HEMTs and that buried parallel 2DHG channels do not exist in MC-HEMTs.